Beneficiation and recovery of indium from liquid-crystal-display glass by hydrometallurgy. (November 2016) - Swain, Basudev; Mishra, Chinmayee; Hong, Hyun Seon; Cho, Sung-Soo
Graphical abstract: Highlights: Indium rich ITO bearing end-of-life LCD panels leached for value recovery. Indium is completely extracted with 5 M HCl at 75 °C. Leaching parameters are optimized for the efficient recovery of indium. An efficient cradle to cradle waste management process for the circular economy. Abstract: Considering indium scarcity, the end-of-life (EOL) LCD, which accounts for up to 90% of market share can be a feasible secondary resource upon successful recycling. In the preferred hydrometallurgical process of such critical metals, leaching is the essential primary and essential phase has been investigated. In this process, LCD was mechanically separated along with other parts from EOL TVs through a smartly engineered process developed at our institute, Institute for Advanced Engineering (IAE), the Republic of Korea. After removing plastics and metals from the LCD, it was mechanically shredded for size reduction. The mechanically shredded LCD waste was leached with HCl for recovery of indium. Possible leaching parameters such as; effect of acid concentration, pulp density, temperature and effect of oxidant H2 O2 concentration were investigated to identify the best conditions for indium extraction. Indium (76.16 × 10 −3 g/L) and tin (10.24 × 10 −3 g/L) leaching was achieved at their optimum condition, i.e. lixiviant of 5 M HCl, a pulp density of 500 g/L, temperature 75 °C, agitation speed of 400 rpm and time for 120 min. At optimum condition the glass, plastic and the valuable metal indium have completely been separated. From indium enriched leach liquor, indium can be purified and recovered through hydrometallurgy.